58-nW 0.5-V Mixed-Mode Universal Filter Using Multiple-Input Multiple-Output OTAs - Fabian Khateb; Montree Kumngern; Tomasz Kulej (My University, 2023)
This paper presents a mixed-mode universal filter using a multiple-input multiple-output operational transconductance amplifier (MIMO-OTA). The multiple-input OTA is designed using the multiple-input MOS transistor technique (MI-MOST), resulting in a single differential pair and minimal power consumption. The MIMO-OTA is used to design a universal mixed-mode filter that provides input and output in voltage and current form. In a single topology, second order filters with low-pass (LP), high-pass (HP), band-pass (BP), band-stop (BS) and all-pass (AP) transfer functions can be obtained in voltage-mode (VM), current-mode (CM), transadmittance-mode (TAM) and transimpedance-mode (TIM). In addition, VM, CM, and TAM offer non-inverting and inverting transfer functions of LP, HP, BP, BS, and AP filters. The natural frequency and quality factor of all filter functions can be orthogonally controlled. Electronic tuning of the natural frequency is provided. The supply voltage is 0.5 V and the power consumption of the filter is 58 nW for 4 nA setting current. The filter was designed and simulated in the Cadence Virtuoso environment using TSMC 0.18μm CMOS technology. The simulation results including Monte-Carlo analysis and process, voltage, and temperature corners are presented.
Keywords: Operational transconductance amplifier; Transimpedance amplifier; Process corners; Analog and Mixed-Signal Circuit Design